HUBUNGAN KONFORMITAS DENGAN PSYCHOLOGICAL DISTRESS PADA REMAJA GENERASI Z - Cantika, Bernada; Huwae, Arthur (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2025)
This study aims to determine the relationship between conformity and psychological distress among Generation Z. adolescents. Adolescence is a transitional period that is vulnerable to social pressure, especially from peer group. Generation Z, who grew up in the digital age with high social media usage, are at greater risk of experiencing anxiety and depression. The study used a quantitative method with a bivariate correlation design. There were 223 participants aged 15-21 years. The instruments used were the Conformity Scale and the Psychological Distress K-10 Scale. Data analysis was performed using Spearman’s correlation test throug SPSS version 24.The result showed a significant positive relationship between conformity and psychological distress. The majority of respondents had high levels of conformity (83,9%) and psychological distress (87,4%).